2012
DOI: 10.1128/aem.02565-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Virulent Phages of Lactobacillus plantarum

Abstract: We characterized two Lactobacillus plantarum virulent siphophages, ATCC 8014-B1 (B1) and ATCC 8014-B2 (B2), previously isolated from corn silage and anaerobic sewage sludge, respectively. Phage B2 infected two of the eight L. plantarum strains tested, while phage B1 infected three. Phage adsorption was highly variable depending on the strain used. Phage defense systems were found in at least two L. plantarum strains, LMG9211 and WCSF1. The linear double-stranded DNA genome of the pac-type phage B1 had 38,002 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…29 In phage B2, only 2 of the 6 tRNA genes corresponded to codons more frequently used by the phage than its Lactobacillus plantarum host. 30 Limor-Waisberg et al looked at cyanophages with very different genome size and GC content: T7-like podoviruses have small genomes, few tRNA genes and only infect hosts with similar GC content, while T4-like myoviruses have larger genomes, more tRNA genes, and can infect hosts that differ in GC content. 21 Among the myoviruses, greater difference in GC content between host and phages was associated with more tRNA genes in these phages.…”
Section: Codon Versus Amino Acid Usagementioning
confidence: 99%
“…29 In phage B2, only 2 of the 6 tRNA genes corresponded to codons more frequently used by the phage than its Lactobacillus plantarum host. 30 Limor-Waisberg et al looked at cyanophages with very different genome size and GC content: T7-like podoviruses have small genomes, few tRNA genes and only infect hosts with similar GC content, while T4-like myoviruses have larger genomes, more tRNA genes, and can infect hosts that differ in GC content. 21 Among the myoviruses, greater difference in GC content between host and phages was associated with more tRNA genes in these phages.…”
Section: Codon Versus Amino Acid Usagementioning
confidence: 99%
“…In fact, among phages that infect Lactobacillus species, the Ldl1 tail length is second only to that of L. plantarum phage B2, which was isolated in 1971 and which was originally reported to display a tail length of 500 nm (33). However, a recent study found the tail length of this phage to be 240 Ϯ 3 nm, with no reasons being given for the discrepancy (34). Also evident is a minihead variant of Ldl1, exhibiting a much smaller head with the long tail still present.…”
Section: Resultsmentioning
confidence: 83%
“…The latter two proteins in turn exhibit similarity to a DNA polymerase III protein (␣ subunit) from Bacillus phage SPBc2 (34). ORF37 Ldl1 also shows 41% identity to a putative DNA polymerase of Bacillus subtilis subsp.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1B and C). This suggested that the major capsid protein was likely processed (27). The ORF10 product (MTP) was also found in two protein bands (bands 8 and 9) with molecular masses of 26 and 22 kDa, respectively.…”
mentioning
confidence: 89%